Restoring Australia’s Freshwater Wetlands: Rural Landholder Perspectives - Elizabeth P Galanis; Lai Ming Lam; Lukas Schuster; Damien Cook; Martino E Malerba (Wetlands, 2026)
Wetlands are among the most productive and biodiverse ecosystems in the world, yet they are also the most threatened. These vital habitats play a crucial role in mitigating climate change. Although most freshwater wetlands occur on private property, limited research exists on landholder perceptions of their ownership and management. We interviewed landholders who participated in a wetland restoration program. Our interviews explored motivations and barriers to participation and the impact of climate change, if any, on landholders. We conducted a thematic analysis of interview transcripts. Our analysis revealed three major themes. First, participants were motivated by the intrinsic value of nature, focusing on benefits to native flora and fauna rather than personal gain. They expressed strong emotional connections to nature and a sense of stewardship. Second, the removal of bureaucratic, financial and practical barriers by a knowledgeable local facilitator was important for participation. Third, participants acknowledged the tension between agricultural practices and the needs of nature, striving to balance these competing demands. Although climate change was recognised, the primary motivator was restoring natural ecosystems. Restoring freshwater wetlands can help policymakers achieve international and domestic biodiversity goals by aligning conservation programs with landholders’ values. Employing local facilitators with intimate knowledge of the community and ecosystem can enhance program engagement. Additionally, integrating agricultural and environmental needs, such as through agritourism, can further support biodiversity, and the economic and mental resilience of landholders.

Cooperative breeding and the emergence of multilevel societies in birds - Ettore Camerlenghi; Alexandra McQueen; Kaspar Delhey; Carly N. Cook; Sjouke A. Kingma; Damien R. Farine; Anne Peters (Ecology Letters, 2022)
Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds.